AN ANALYSIS OF DISTANCE LEARNING ON ATTITUDES AND LEARNING INTERESTS OF JUNIOR HIGHT SCHOOL STUDENTS IN SCIENCE SUBJECTS IN SUBDISTRICT IV JURAI - Kurnia Safriani; Tuti Lestari (Department of Science Education, 2022)
The world has entered the industrial revolution 4.0 era and it is going to welcome the society 5.0 era. This industrial revolution era is characterized by the development of ICTs which is very fast. It is also an impact on education began to lead in online or blended learning. Therefore, the schools and students should be able to adapt to Online Distance Learning (ODL). As a result of the Covid-19 pandemic, the schools in all regions of Indonesia are required to implement ODL, including SMPN IV Jurai Subdistrict. This study used used descriptive quantitative research using the survey method. This study aimed to analyze the ODL attitudes and Junior High School students’interest in Natural Science subjects in the IV Jurai Subdistrict. The population of this study was all Junior High School students in the IV Jurai Subdistrict that consisted of 7 Junior High School with 2,130 students in total. The sampling technique used was the Slovin technique and it obtained a sample of 399 students. Furthermore, the data were collected by distributing questionnaires. The research data were analyzes using percentage calculations by determining the categories of students’ attitudes and learning interests in Natural Science subjects. The results showed that the students’ learning attitudes as a whole were in the moderate category with a percentage of 71.48%. while the overall students’ interest has a high category with a percentage of 68.39%.